Does Two‐Dimensional Image Reconstruction from Three‐Dimensional Full Volume Echocardiography Improve the Assessment of Left Ventricular Morphology and Function?. Issue 1 (11th September 2012) - Amzulescu, Mihaela Silvia; Slavich, Massimo; Florian, Anca; Goetschalckx, Kaatje; Voigt, Jens‐Uwe
<x xml:space="preserve">Abstract</x> Aims: (i) To investigate geometric differences between apical views of the left ventricle (LV) derived from standard 2D echocardiography (std2D) and triplane (TP) views, as well as the "ideally" reconstructed 2D (rec2D) views derived from 3D full volume (3DFV) acquisitions, and their influence on the assessment of LV morphology and function. (ii) To determine the feasibility and accuracy of the automatic reconstruction of 2D apical views from 3DFV datasets. Methods and results: In 59 patients with structurally normal, dilated, and hypertrophic hearts, rec2D was reconstructed manually and automatically and compared to std2D, TP, and 3DFV regarding the image plane orientation (true vs. ideal probe position, plane intersection angles), LV dimensions, volumes, and EF. The ideal probe position deviated from the true one by 6.9 ± 4.1 mm and 9.5 ± 4.5 mm, for manually and automatically rec2D, respectively, regardless of LV geometry. The mean difference±SD between manual and automatic reconstruction was −2.5 ± 4.4 mm. LV long axis was measured minimally, but significantly longer in rec2D than std2D and TP. LV volumes and EF did not differ between methods. The intersection angle of the two‐chamber view and the three‐chamber view with the four‐chamber view for manual and automatic reconstruction was 53°±7° and 129°±7° and 60° and 130°, respectively. Conclusion: Ideal reconstruction of nonforeshortened 2D images from 3DFV does not lead to a relevant improvement in image geometry or the assessment of LV morphology and function. The automatic reconstruction algorithm deviates only slightly from manual results.